Hubungan Pengetahuan Dan Dukungan Guru Dengan Kepatuhan Mengonsumsi Tablet Tambah Darah (TTD) Pada Remaja Putri Di SMAN 4 Tana Toraja - Hayuti Windha Pagiu; Lucia Yogyana Suramas; Sriwahyuni Sriwahyuni (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Giving blood supplement tablets to teenagers should be a very appropriate intervention. Iron deficiency in teenagers is dangerous if not treated properly. This research aims to determine the relationship between teacher knowledge and support and compliance with TTD consumption among young women at SMAN 4 Tana Toraja. The research design used is a quantitative approach. The population in this study were 307 female students in class XI and XII at SMAN 4 Tana Toraja with a total sample of 75 female students. Sampling used the Stratified Random Sampling technique and data collection using a questionnaire then processing the data with the help of the SPSS application using the Chi-Square test. The results of the research show that there is a relationship between knowledge and compliance with consuming Blood Addition Tablets (TTD) among young women at SMAN 4 Tana Toraja, with a p-value = 0.001 < 0.05 and there is a relationship between teacher support and compliance with consuming Blood Addition Tablets (TTD ) in young women at SMAN 4 Tana Toraja, with a p-value = 0.000 < 0.05. It can be concluded that the higher the knowledge of female students and the support from teachers can also influence the compliance of female students in consuming Blood Supplement Tablets (TTD) among young women at SMAN 4 Tana Toraja.